ANALISIS AKUNTANSI UNTUK PERSEDIAAN OBAT GENERIK BERDASARKAN PADA PSAP NO. 05 DI RSUD ABDOEL WAHAB SJAHRANIE SAMARINDA - Nirwana, Ros; Lau, Elfreda Aplonia; Kulsum, Umi (RJABM (Research Journal of Accounting and Business Management), 2019)
This reseach aim to compare recording and drugs inventory especially characterized generic drug by the largest transaction and drugs that often out of stock. Generic drugs consist of five types of generic injection and five types of tablets, spesifically NaCl 0,9% 500 Ml Inj, Ranitidin Inj, Dexamethasone 5 Ml Inj, Cefotaxime 1 g Inj, Gentamicin 80 Mg Inj, Amoxicillin 500 Mg, Antasida Doen, Dexamethasone 0,5 Mg, Chlorpeniramin, and Lansoprazol from January 1st to December 31st 2018 at RSUD Abdoel Wahab Sjahrani Samarinda on Palang Merah street Samarinda Indonesia, according to recording and aassessment stock of generic drugs river to PSAP No 05 of 2010.Methods in this comparison were Perpetual Method and First In First Out(FIFO) Method based on PSAP No. 05 of 2010. The results of this research were the recording and assessment of generic drug supplies at Abdoel Wahab Sjahranie Samarinda General Hospital  not in accordance with PSAP No. 05 of 2010